Stability of commercial phytase products under increasing thermal conditioning temperatures - De Jong, J. A.; DeRouchey, Joel M.; Tokach, Michael D.; Goodband, Robert D.; Woodworth, Jason C.; Jones, Cassandra K.; Stark, Charles R.; Bradley, C. L.; Loughmiller, J. A.; Bergstrom, J. R. (My University, 2016)
The objective was to determine the stability of 4 commercial phytase products exposed to increasing thermal conditioning temperatures. The 4 commercial products used were: Quantum Blue 5G (AB Vista, Marlborough, United Kingdom); Ronozyme Hi Phos GT (DSM Nutritional Products, Parsippany, NJ); Axtra Phy TPT (Dupont, Wilmington, DE), and Microtech 5000 Plus (Guangdong VTR Bio-Tech Co., Ltd., Guangdong, China). The phytase products were mixed as part of a corn-soybean meal-based swine diet at a concentration recommended by the manufacturer to provide a 0.12% aP release. Diets were exposed to each of 4 thermal conditioning temperatures (65, 75, 85, and 95°C) for approximately 40 s and the entire process was repeated on 4 consecutive days to create 4 replicates. Samples were taken while feed exited the conditioner and before entering the pellet die. Phytase activity was determined from complete feed samples before conditioning to establish a baseline diet phytase activity level for each product. Phytase stability was measured as the residual phytase activity (% of initial) at each conditioning temperature. There were no product × temperature interactions for conditioning temperature, throughput, or residual phytase activity. As expected, as the target temperature was increased, conditioning temperature increased (linear, P < 0.001) and conditioner throughput decreased (linear, P < 0.001). As target temperature increased, phytase activity decreased (linear, P < 0.001) for each product. There was a significant phytase product main effect which was primarily caused by Microtech 5000 Plus having decreased (P < 0.05) phytase activity when compared to all other products at all conditioning temperatures. In summary, increasing conditioning temperatures decreased phytase stability regardless of product. In addition, Microtech 5000 Plus had decreased residual phytase activity (% of initial) when compared to all other products.
Citation: De Jong, J. A., DeRouchey, J. M., Tokach, M. D., Goodband, R. D., Woodworth, J. C., Jones, C. K., . . . Bergstrom, J. R. (2016). Stability of commercial phytase products under increasing thermal conditioning temperatures. Journal of Animal Science, 94, 101-101. doi:10.2527/msasas2016-214
Keywords: Conditioning Temperature; Pelleting; Phytase Stability; Agriculture